Hypertension treatment in the practice of the general practitioner in light of the current guidelines of the Polish Society of Hypertension - Bryl, Wiesław; Springer, Michał (Lekarz POZ, 2017)
Arterial hypertension is one of the most common diseases in primary care practice. It is also one of the most widespread diseases in the adult population, and its occurrence and intensity correlate with higher cardiovascular risk. Correct treatment of arterial hypertension and comprehensive supervision of patients can significantly reduce the risk and the amount of connected deaths. The primary care physician plays a responsible role in the diagnostics, treatment, and monitoring process of patients with arterial hypertension.